1998
DOI: 10.1080/00926239808404921
|View full text |Cite
|
Sign up to set email alerts
|

Effects of child and adult sexual abuse on adult sexuality

Abstract: The differential effects of child and adult sexual abuse on adult sexual functioning were examined. The Golombok Rust Inventory of Sexual Satisfaction (GRISS) and a sexual experiences questionnaire were administered to 201 psychology students at the University of South Florida, 175 of whom were retained in the study. GRISS variables that were analyzed consisted of anorgasmia, sexual avoidance, sexual dissatisfaction, sexual noncommunication, nonsensuality, and vaginismus. Women who were sexually abused in adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
42
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(47 citation statements)
references
References 21 publications
5
42
0
Order By: Relevance
“…However, other age cut-offs have also been reported, including age 17 (e.g., Paul, Catania, Pollack, & Stall, 2001;Walser & Kern, 1996) age 16 (e.g., Bartoi & Kinder, 1998;Kalichman, Gore-Felton, Benotsch, Cage, & Rompa, 2004), age 15 (e.g., Jinich et al, 1998;Mayall & Gold, 1995), age 14 (e.g., Merrill, Guimond, Thomsen, & Milner, 2003), and age 13 (e.g., Carballo-Dieguez & Dolezal, 1995;DiIorio, Hartwell, & Hansen, 2002).…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…However, other age cut-offs have also been reported, including age 17 (e.g., Paul, Catania, Pollack, & Stall, 2001;Walser & Kern, 1996) age 16 (e.g., Bartoi & Kinder, 1998;Kalichman, Gore-Felton, Benotsch, Cage, & Rompa, 2004), age 15 (e.g., Jinich et al, 1998;Mayall & Gold, 1995), age 14 (e.g., Merrill, Guimond, Thomsen, & Milner, 2003), and age 13 (e.g., Carballo-Dieguez & Dolezal, 1995;DiIorio, Hartwell, & Hansen, 2002).…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
“…Women who were incarcerated were more likely to have traded sex, to have engaged in unprotected anal sex, had multiple partners, had sex with someone who injects drugs, and to be infected with HIV (McClanahan, McClelland, Abram, & Teplin, 1999;Mullings, Marquart, & Brewer, 2000;Stevens et al, 1995). Among homeless women, CSA was associated with sex trading (Simons & Whitbeck, 1991).A few studies failed to find hypothesized differences between CSA and non-CSA groups on some sexual behavior outcomes, including age at first intercourse, the number of sexual partners, the frequency of intercourse, the frequency of condom use, the frequency of sex while using drugs, having an STD, or HIV status (Bartoi & Kinder, 1998;Medrano, Desmond, Zule, & Hatch, 1999;Noell, Rohde, Seeley, & Ochs, 2001;Vlahov et al, 1998). Relatively small samples of women reporting CSA may have led to low power to detect a small effect in some of these studies (e.g., Bartoi & Kinder, 1998;Medrano et al, 1999;Noell et al, 2001).…”
mentioning
confidence: 99%
“…This has been documented in clinical populations and populations at high risk of contracting HIV (Cunningham, Stiffman, Dor6, & Earls, 1994;Parillo, Freeman, Collier, & Young, 2(X)1; Tsai, FeldmanSununers, & Edgar, 1979;Walser & Kern, 1996;Zierler et al, 1991) as well as in undergraduate (Johnsen & Harlow, 1996) and community (Wyatt, 1988) samples. However, a number of other studies have found no relationship between CSA and number of sex partners (Bartoi & Kinder, 1998;Noll, Trickett, & Putnam, 2000;Widom & Kuhns, 1996).…”
mentioning
confidence: 99%
“…In studies comparing sexually abused and nonabused women, abused women reported more negative reactions to sex (Charmoli & Athelstan, 1988;E. Gold, 1986;Johnsen & Harlow, 1996), more sexual avoidance (Matorin, 1999; but see Bartoi & Kinder, 1998), more sexual aversion (Wenninger & Heiman, 1998), and less sexual arousal (Fleming, Mullen, Sibthorpe, & Bammer, 1999;Wenninger & Heiman, 1998). In addition, compared with nonabused women, sexually abused women reported more sexual problems (Elliott & Briere, 1992;Fleming et al, 1999;Mullen, Martin, Anderson, Romans, & Herbison, 1996) and a greater prevalence of sexual disorders (Saunders, Villeponteaux, Lipovsky, Kilpatrick, & Veronen, 1992).…”
mentioning
confidence: 99%
“…Women presenting for a third or more abortions were more than 2.5 times as likely as those seeking a first abortion to report a history of sexual abuse [6] . Study results are inconsistent, however [1,8] . Women with a history of CSA may have reduced confidence in their abilities as a mother [11] , as well as difficulties in using contraception reliably [7,28,36] .…”
Section: Abortionsmentioning
confidence: 69%